Compact planar ultrawideband MIMO antenna for wireless applications - P. Pavithra; A. Sriram; K. Kalimuthu (International Journal of Advances in Applied Sciences, 2019)
A compact microstrip fed printed monopole MIMO antenna with ultrawideband (UWB) frequency response (S11< -10 dB for 3.1-10.6 GHz) is proposed in this paper. The proposed antenna is miniaturized and has a high isolation of > 23 dB between the ports compared to the existing UWB multiinput multi output (MIMO) antennas in the literature. The proposed antenna is built on FR4 substrate with thickness of 1.6 mm using all-digital single chip architecture and it is planar in geometry to be easily integrated with the other electronic components in the printed circuit board (PCB). The UWBMIMO antenna is analyzed using simulation and measurements and its performance is investigated. The antenna is extremely useful for low power short range communications and it provides high multipath immunity due  to diversity.